Multiscalar Institutional Work of System-Building Sustainable Entrepreneurs in Transitioning Coal Regions: A Case of an Energy Cluster - Stasik, Agata; Dańkowska, Alicja (Social Entrepreneurship Review, 2024)
Background: Social enterprise is a potential driver of sustainability at the community level in energy sector decarbonization.Research objectives: We ask how sustainable entrepreneurs’ embeddedness in the territorial and institutional contexts of a coal region in transition shapes their ability to exploit sustainable business opportunities, and how they can influence energy transition pathways.Research design and methods: We introduce the notion of system-building sustainable entrepreneurs, who develop breakthrough niche innovations. Our analytical framework employs a multilevel perspective and multiscalar analysis of institutional work is applied to the case study of an energy cluster.Results: We identified multiscalar institutional work of SBSEs operating in the niche, presenting the inhibiting and enabling factors at the regime and landscape levels. Although enabling factors created opportunities, they could only be exploited through institutional work.Conclusions: We identified three key factors shaping the ability of system-building sustainable entrepreneurs to exploit opportunities and shape transition pathways.